After the Implant-a Study on Post Cochlear Implant Rehabilitation of Congenitally Deaf Children - Mashhadi, Syed Fawad; Khan, Nazish; Malik, Izza Afaq; Anwaar, Rahma; Sultan, Hadia; Shahbaz, Rohma (Pakistan Armed Forces Medical Journal, 2024)
Objectives: To assess the perceptions and compliance of parents/guardians of children with cochlear implant regarding postcochlear implant rehabilitation of their children.Study Design: Analytical, cross-sectional, quantitative studyPlace and Duration of Study: ENT department, Combined Military Hospital, Rawalpindi Pakistan, from Nov 2021 to Apr2022.Methodology: The study was conducted on a sample size of 93 parents/guardians of congenitally deaf children (recipients of cochlear implant) who were recruited via purposive sampling. Parents/guardians of children having severe to profound hearing loss, who did not benefit from hearing aid were included in the study from which those having a hearing age of less than 9 months were excluded. A validated modified questionnaire was adopted and data was collected from the parents/guardians by interviewing them on calls. Data was analyzed by using SPSS 25.Results: Amongst the study participants, 11(11.8%), 30(32.3%), 44(47.3%) and 8(8.6%) parents/guardians showed poor, fair, good and excellent compliance respectively. Better compliance was associated with positive parental (p-value=0.007) and child (p-value=0.004) attitude. Distance 68(73%) and finance 70(75%) were the hurdles faced; irrespective of compliance. However,financial difficulties (p-value=0.585), difficulties due to distance (p-value=0.210) and parental education level (p-value=0.175) were not significantly associated with compliance.Conclusion: The study showed that most parents/guardians 82 (88%) were compliant with the rehabilitation. Positive counselling of the parents and children can further improve compliance. Rehabilitation can be eased with financial assistance and improved accessibility.